Constitution for a Disunited Nation : On Hungary's 2011 Fundamental Law - Tóth, Gábor Attila, 1970- (Book collections on Project MUSE., 2012)
This collection is the most comprehensive account of the Fundamental Law and its underlying principles. The objective is to analyze this constitutional transition from the perspectives of comparative constitutional law, legal theory and political philosophy. The authors outline and analyze how the current constitutional changes are altering the basic structure of the Hungarian State. The key concepts of the theoretical inquiry are sociological and normative legitimacy, majoritarian and partnership approach to democracy, procedural and substantive elements of constitutionalism. Changes are also examined in the field of human rights, focusing on the principles of equality, dignity, and civil liberties.